Initial investigation of land subsidence using GPS data and rigorous analysis - Setan, Halim; Ibrahim, M. S.; Matori, A. N.; Mohd. Saat, S. (2004)
This research attempts to combine geophysical and Global Positioning System (GPS) data via Geographical Information System (GIS) to investigate the land subsidence phenomena. This paper discusses the land subsidence detection procedure using GPS via rigorous analysis, together with the initial results. For testing purpose, two epochs of GPS data (in RINEX format) were collected from 4 stations via static mode using dual frequency GPS receivers. Data for each epoch were imported into PINNACLE software for the computation of GPS baseline vectors (using precise ephemeris). The output from PINNACLE was exported into NGS Blue Book format, and used as input (via a special interface program CONVERT) for network adjustment using STARNET software. Consequently, the results from STARNET were used as input (via program CONVERT) for rigorous deformation analysis using our in-house developed software (GPSAD2000). The results show the practicality of the data processing procedure using PINNACLE, STARNET, CONVERT and GPSAD2000.